Substitution mechanisms of zirconolite for nuclear waste form: a mini review - Ji, Shiyin; Zhao, Chuanhang; Ji, Xiuhua; Gu, Chengxin; Zhang, Youkui; Chen, Xin; Duan, Tao; Ju, Tianhua; Liao, Changzhong (Frontiers in Environmental Science, 2025)
Zirconolite waste forms are advanced ceramic materials for the immobilisation of HLW, particularly actinides. This paper presents a systematic review of seven common substitution mechanisms of nuclear wastes in zirconolite, categorized into two types: charge-compensated substitution and direct substitution. For those substitution modes, three primary phase evolution pathways were identified: i zirconolite-2M to zirconolite-4M and/or to pyrochlore; ii zirconolite-2M to zirconolite-3O; iii zirconolite-2M to zirconolite-3T. The formation of zirconolite-3T or zirconolite-4M as intermediate phases is typically influenced by substitution behaviour, preparation conditions, or fabrication methods. Additionally, the substitution mechanisms of actinides (or REE analogue) in zirconolite were systematically investigated, corresponding to the seven substitution designs. Notably, the preferential occupation of An/REE in Ca sites was verified at simultaneous direct substitution in both Ca and Zr sites. Whilst extensive studies has explored An/REE substitution mechanisms in zirconolite and identified phase evolution pathways to zirconolite-3O, -3T, -4M, and pyrochlore, the substitution behaviour, radiation stability and chemical durability of these defect-fluorite derivatives warrant further systematic investigation.